Meningkatkan Kemampuan Guru Dalam Menyusun Kelengkapan Mengajar Melalui In-House Training di SMP Negeri 1 Lubuk Pakam - Jumiem Jumiem; Zainul Bakri Nasution (Center for Research and Community Service (LPPM) University of Abulyatama, 2019)
The purpose of this study is to improve the ability of teachers in compiling teaching materials through In-House training at SMP 1 Lubuk Pakam. The significant of the study: 1) the principal can solve the teachers’ problems in preparing the completeness of the teaching, 2) improving the ability of the teacher in preparing the completeness of teaching, 3) improving the quality of teaching that affects the quality of the school. The study was conducted in School Action Research in 2 cycle. The data was carried out with a descriptive model, as a result of the weaknesses of the actions in each cycle that will be reflected as improvement material in the next cycle. After the action research is carried out, the results are obtained that: 1). The teachers have a high motivation to participate in the In-House Training and have a strong desire to complete the teaching and will use the completeness of the teaching as supporting the learning process; 2) In Cycle I there were 37.97% teachers who successfully completed the preparation of teaching completeness and in Cycle II there were 81.50% teachers who successfully completed the preparation of teaching completeness. So there is an increase in the teachers’ ability to arrange teaching completeness by 43.53%.